After the Arab revolutions : decentring democratic transition theory - El-Affendi, Abdelwahab; ʻAnānī, Khalīl (Edinburgh University Press Ltd, 2021)
Incorporates the lessons learned from the 2011 Arab revolutions into democratic transition theory.